1996
DOI: 10.1074/jbc.271.24.14098
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a Ku86 Variant Protein That Results in Altered DNA Binding and Diminished DNA-dependent Protein Kinase Activity

Abstract: Three proteins known to play a critical role in mammalian DNA double-strand break repair and lymphoid V(D)J recombination are the autoantigens Ku86 and Ku70 and a 465-kDa serine/threonine protein kinase catalytic subunit (DNA-PKcs). These proteins physically associate to form a complex (DNA.PK) with DNA-dependent protein kinase activity. In this study, we demonstrate using electrophoretic mobility shift assays (EMSAs) that the nuclear DNA end-binding activity of Ku is altered in the human promyelocytic leukemi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
39
0

Year Published

1998
1998
2010
2010

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(43 citation statements)
references
References 62 publications
(77 reference statements)
4
39
0
Order By: Relevance
“…Similar expression of a variant form of the Ku86 protein (but in addition to the full-length protein) has been recently reported in the promyelocytic leukemia cell line, HL60 (Han et al, 1996). The variant form of the Ku86 protein detected in B-lymphocytes presents similarities with the protein detected in HL60 cell line.…”
Section: Characteristics Of the Variant Ku86 Proteinsupporting
confidence: 77%
See 1 more Smart Citation
“…Similar expression of a variant form of the Ku86 protein (but in addition to the full-length protein) has been recently reported in the promyelocytic leukemia cell line, HL60 (Han et al, 1996). The variant form of the Ku86 protein detected in B-lymphocytes presents similarities with the protein detected in HL60 cell line.…”
Section: Characteristics Of the Variant Ku86 Proteinsupporting
confidence: 77%
“…At the present time, the domain(s) responsible for the interaction between Ku86 or the Ku heterodimer with the catalytic component of the DNA-PK CS complex remain(s) unknown. The inability of the mAb 111 (aa 610 ± 705) to recognize the variant form of Ku86 in the HL60 cell line (Han et al, 1996) and in PBL (Ajmani et al, 1995) and of the mAb 150 (aa 490 ± 707) to supershift Ku70/variant Ku86⋅DNA complexes (our results) may implicate the C-terminal part of the protein in this function. However, only reconstitution studies with various deletion mutants of the Ku86 protein will allow this question to be answered since conformational changes induced in the Ku86 variant (and not the region deleted) can be discounted for the decreased ability to recruit DNA-PK CS .…”
Section: Characteristics Of the Variant Ku86 Proteinmentioning
confidence: 54%
“…Ku binds directly to free DNA termini in a non-sequence-specific manner (Mimori and Hardin, 1986;Blier et al, 1993;Falzon et al, 1993), which activates DNA-PK cs to form the DNA-PK complex (Yaneva et al, 1997;Calsou et al, 1999;Singleton et al, 1999). Studies with cells harboring aberrant Ku proteins have indicated that DNA-PK cs binds to the carboxyterminal region of Ku80 (Han et al, 1996a;Muller and Salles, 1997), which is essential for activation of DNA-PK activity (Gell and Jackson, 1999;Singleton et al, 1999). DNA-PK cs also phosphorylates Ku70 at serine 6 and Ku80 at serines 577, 580, possibly serine 579, and threonine 715 (Chan et al, 1999).…”
Section: Dna-pk Interactions Within the Nhej Machinarymentioning
confidence: 99%
“…23 The 25-mer dsDNA was prepared as described previously. 45 For band shift assay, 0.1 ng of 32 P-labeled DNA (100,000 cpm) was incubated with 2.5 g of cell extracts and 1 g of closed circular plasmid DNA as a nonspecific competitor in 20 L of binding buffer (10 mM tris(hydroxymethyl)aminomethaneHCl (pH 8.0), 1 mM ethylenediaminetetraacetic acid, 10% glycerol, and 50 mM KCl) at room temperature for 10 minutes. The samples were electrophoresed on a 4% polyacrylamide gel at 4°C for 2 hours at 100 V. The gel was dried on Whatman paper and exposed to x-ray film.…”
Section: Band Shift Assaymentioning
confidence: 99%
“…As described previously, 45 we used a 25-mer ds probe for analysis by EMSA. As shown on Figure 2A, a unique DNA-protein complex that correspond to Ku DNA end binding activity (complex C) was detected.…”
Section: Activity Of the Two Subunits Of Dna-pk Complexmentioning
confidence: 99%